Penggunaan Situs Kemendesa.go.id sebagai Sumber Informasi Program Kemendesa: Studi Kasus di Kabupaten Bogor - Intyaswati, Drina; Abdullah, Ahmad Zaki; Mardani, Puri Bestari (Jurnal Studi Komunikasi, 2018)
In order to improve the welfare of rural communities in Indonesia, development needs to be carried out in various aspects to catch up. Ministry of Rural as the ministry responsible for development in the village has socialized the program through website kemendesa.go.id. The website provides information about village priority programs, utilisation of village funds, village business entities, and village superior products. Studies conducted on the villages in the area of Bogor Regency conducted to see how the utilization of information resources from Ministry of Rural through the internet media. By interviewing officials from ten villages and observation of village infrastructure means that the information submitted by Ministry of Rural through the website kemendesa.go.id has not been well received by the village officials. Still needed support from the government especially the availability of facilities that support ease of internet access.